An Analysis of Swear Words Translation in Joker Movie - Dhanu Ario Putra; Merry Rullyanti; Veronica Giofani; Sofia Sahiro (Literary Criticism, 2020)
This qualitative descriptive study intends to examine the equivalence technique in the English-Bahasa Indonesia translation of slang and profanity in the film Joker. The formal and dynamic equivalences concept proposed by Nida (1964) serves as the theoretical framework for this study. Prior to equivalence analysis, slang and curse words were identified. This study employed two concepts for identification: Yule's (1996) word formation processes and Finegan's (2004) lexical semantics. The investigation identified 24 swear words terms. And most of translation technique used in translating swear words is Literal, appearing 21 times from this research, it can be concluded that Joker the movie didn’t use a lot of swear words even though the main character is evil. Keywords: swear words, translation, Joker